The battle for employment guarantee - Khera, Reetika (New Delhi : Oxford University Press, 2011)
Contributed articles.
Includes bibliographical references (p. [279]-296) and indexes.
Keywords: India; MANPOWER POLICY, RURAL -- INDIA; RURAL POOR -- EMPLOYMENT -- INDIA; BASIC INCOME -- INDIA